Diagnostic Accuracy of Renal Mass Biopsy: An Ex Vivo Study of 100 Nephrectomy Specimens. (May 2016) - von Rundstedt, Friedrich-Carl; Mata, Douglas Alexander; Kryvenko, Oleksandr N.; Roth, Stephan; Degener, Stephan; Dreger, Nici Markus; Goedde, Daniel; Assaid, Ahmed; Kamper, Lars; Haage, Patrick; Stoerkel, Stephan; Lazica, David A.
We investigated the diagnostic accuracy of renal mass biopsy in an ex vivo model, as well as compared the agreement of the preoperative radiological diagnosis with the final pathologic diagnosis. Two 18-gauge needle-core and 2 vacuum-needle biopsies were performed ex vivo from the tumors of 100 consecutive patients undergoing radical nephrectomy between 2006 and 2010. The median tumor size was 5.5 cm. There was no significant difference with regard to cylinder length or tissue quality between the sampling methods. At least 1 of 4 needle cores contained diagnostic tissue in 88% of patients. Biopsy specimens identified clear cell (54%), papillary (13%), or chromophobe (5%) renal cell carcinoma; urothelial carcinoma (6%); oncocytoma (5%); liposarcoma (1%); metastatic colorectal carcinoma (1%); squamous cell carcinoma (1%); unclassified renal cell neoplasm (1%); and no tumor sampled (12%). The sensitivity of the biopsy for accurately determining the diagnosis was 88% (95% CI: 79% to 93%). The specificity was 100% (95% CI: 17% to 100%). Biopsy grade correlated strongly with final pathology (83.5% agreement). There was no difference in average tumor size in cases with the same versus higher grade on final pathology (5.87 vs 5.97; P = .87). Appraisal of tumor histology by radiology agreed with the pathologic diagnosis in 68% of cases. Provided that the biopsy samples the tumor tissue in a renal mass, pathologic analysis is of great diagnostic value in respect of grade and tumor type and correlates well with excisional pathology. This constitutes strong ground for increasingly used renal mass biopsy in patients considering active surveillance or ablation therapy.